1993
DOI: 10.1016/0014-5793(93)81550-j
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C isoenzymes in human neuroblasts involvement of PKCε in cell differentiation

Abstract: Although neuronal cells are a major target of phorbol ester action, the activity of the various protein kinase C (PKC) isoenzymes have not been studied in detail in human neuroblasts. Differentiation of the LAN-5 human neuroblastoma cell line by interferon-y (IFN-y) is accompanied by a twofold increase in PKC activity. Since PKC is a multigene family, we investigated which isoforms were expressed in control and differentiated cells, and which of these isoenzymes is involved in neuronal differentiation. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Intestinal cells (including Caco-2 cells) express at least 10 isoforms of PKC, including PKC-␣, PKC-␤1, PKC-␤2, PKC-␦, PKC-⑀, PKC-, PKC-, PKC-, PKC-, and PKC- (McKenna et al, 1995;Maruvada and Levine, 1999;Banan et al, 2001aBanan et al, ,b, 2002aBanan et al, , 2003aBanan et al, ,b, 2004. These isozymes differ in their mechanism of activation, subcellular distribution, substrate type, and expression, suggesting that each of these PKC isoforms can perform unique biological tasks (Persons et al, 1988;Melloni et al, 1990;Mischak et al, 1993;Ponzoni et al, 1993;Banan et al, 2002aBanan et al, , 2003aBanan et al, , 2004. In our previous studies, we demonstrated both damaging and protective mechanisms/pathways affecting gut barrier integrity and permeability.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Intestinal cells (including Caco-2 cells) express at least 10 isoforms of PKC, including PKC-␣, PKC-␤1, PKC-␤2, PKC-␦, PKC-⑀, PKC-, PKC-, PKC-, PKC-, and PKC- (McKenna et al, 1995;Maruvada and Levine, 1999;Banan et al, 2001aBanan et al, ,b, 2002aBanan et al, , 2003aBanan et al, ,b, 2004. These isozymes differ in their mechanism of activation, subcellular distribution, substrate type, and expression, suggesting that each of these PKC isoforms can perform unique biological tasks (Persons et al, 1988;Melloni et al, 1990;Mischak et al, 1993;Ponzoni et al, 1993;Banan et al, 2002aBanan et al, , 2003aBanan et al, , 2004. In our previous studies, we demonstrated both damaging and protective mechanisms/pathways affecting gut barrier integrity and permeability.…”
mentioning
confidence: 63%
“…PKC consists of a family of serine-and threonine-specific kinases, which includes at least 12 known isoenzymes that can be classified into three subfamilies (Housey et al, 1988;Ponzoni et al, 1993;Maruvada and Levine, 1999;Banan et al, 2001aBanan et al, ,b, 2002aBanan et al, , 2003aBanan et al, ,b, 2004: conventional (or "classical") PKC isoforms (␣, ␤1, ␤2, and ␥), "novel" PKC isoenzymes (␦, ⑀, , , and ), and "atypical" PKC isoforms (, , and ). Intestinal cells (including Caco-2 cells) express at least 10 isoforms of PKC, including PKC-␣, PKC-␤1, PKC-␤2, PKC-␦, PKC-⑀, PKC-, PKC-, PKC-, PKC-, and PKC- (McKenna et al, 1995;Maruvada and Levine, 1999;Banan et al, 2001aBanan et al, ,b, 2002aBanan et al, , 2003aBanan et al, ,b, 2004.…”
mentioning
confidence: 99%
“…Among classical PKCs, IFN-␥ has recently been shown to activate PKC␣, which stimulates STAT1␣ to increase transcription of ICAM-1 from a GAS element present in its promoter (57). In neuronal cells, IFN-␥ increases expression of the novel PKC⑀ (58). Also a role of PKC⑀ has been suggested in inflammation-induced pain (59).…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines and methods have been previously described in detail (15,16,(26)(27)(28)(29). Briefly, GI-CA-N and LAN-5 cells were harvested with PBS, resuspended in RPMI 1640, and seeded on 96-well plates (Costar, Cambridge MA) previously coated with ECM substrates or tat residues (10 f-Lg/ml final concentration on plastic plates preactivated with bis-bromo-sulfosuccynimidyl-suberate, BS3, Pierce).…”
Section: Methodsmentioning
confidence: 99%
“…NB cells proliferation was evaluated by eH]TdR incorporation as described before in detail (23). Morphologic and immunophenotype changes were also evaluated by mean of immunocytochemistry as described elsewhere (15,16,(26)(27)(28)(29). Briefly, the percent of positive cells was evaluated by two different researchers, blind to study senses.…”
Section: Methodsmentioning
confidence: 99%